Education and its conceptualization as an autonomous technique: and analysis based on the work of Jacques Ellul - IGELMO ZALDÍVAR, Jon; JOVER OLMEDA, Gonzalo; QUIROGA UCEDA, Patricia (Utopía y Praxis Latinoamericana, 2021)
In this article we return to the ideas of Jacques Ellul in the context of the technologicalization of education. We take as a reference for the analysis the book entitled The Technoligical Society. The starting idea of this work by Ellul is that societies began in the second half of the 20th century a historical period under the dominance of technique. In an educational perspective, it is possible to observe a drift towards the rationalization, systematization and sequencing of the teaching and learning processes, under the premise that education can be conceptualized as an autonomous technique.